2005
DOI: 10.1080/09638230500389105
|View full text |Cite
|
Sign up to set email alerts
|

The nature and purpose of acute psychiatric wards: The tompkins acute ward study

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 17 publications
1
85
0
Order By: Relevance
“…53 Previous studies evaluating the acceptability and/or use of different containment methods in mental health services 4,45,54 have not considered the association between access to seclusion and/or PICUs and acceptability/use of different containment methods. Those that have considered ratings of acceptability have shown that staff rate seclusion as less acceptable than nearly every other form of containment and PICU care as one of the most acceptable forms of containment.…”
Section: Discussionmentioning
confidence: 99%
“…53 Previous studies evaluating the acceptability and/or use of different containment methods in mental health services 4,45,54 have not considered the association between access to seclusion and/or PICUs and acceptability/use of different containment methods. Those that have considered ratings of acceptability have shown that staff rate seclusion as less acceptable than nearly every other form of containment and PICU care as one of the most acceptable forms of containment.…”
Section: Discussionmentioning
confidence: 99%
“…This is commonly referred to as their 'social network' (Johnson et al 2008). This social network is essential in resolving the mental health crisis and without their involvement, the person with mental health problems may be admitted to hospital for treatment (Bowers et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These are "providing safety for the patient and others, collecting and communicating information about patients, giving and monitoring treatment, tolerating and managing disturbed behavior, providing personal care, and managing an environment where patients can comfortably stay". In order to carry out these case-by-case cares, it is required in the ACU that nurses promptly assess the present condition of the patient and perform necessary nursing care [8]. For that purpose, it was considered to be necessary to acquire the information concerning the patient's ability to understand, the developmental stage, current treatment performed, and any relapsing condition of the psychiatric disease.…”
Section: Assessment Items Priority In the Acumentioning
confidence: 99%